DDR1 Affects Metabolic Reprogramming in Breast Cancer Cells by Cross-Talking to the Insulin/IGF System - Veronica Vella; Marika Giuliano; Maria Luisa Nicolosi; Maria Giovanna Majorana; Małgorzata Anna Marć; Maria Grazia Muoio; Andrea Morrione; Marcello Maggiolini; Rosamaria Lappano; Ernestina Marianna De Francesco; Antonino Belfiore (Biomolecules, 2021)
The insulin receptor isoform A (IR-A), a dual receptor for insulin and IGF2, plays a role in breast cancer (BC) progression and metabolic reprogramming. Notably, discoidin domain receptor 1 (DDR1), a collagen receptor often dysregulated in cancer, is involved in a functional crosstalk and feed forward loop with both the IR-A and the insulin like growth factor receptor 1 (IGF1R). Here, we aimed at investigating whether DDR1 might affect BC cell metabolism by modulating the IGF1R and/or the IR. To this aim, we generated MCF7 BC cells engineered to stably overexpress either IGF2 (MCF7/IGF2) or the IR-A (MCF7/IR-A). In both cell models, we observed that DDR1 silencing induced a significant decrease of total ATP production, particularly affecting the rate of mitochondrial ATP production. We also observed the downregulation of key molecules implicated in both glycolysis and oxidative phosphorylation. These metabolic changes were not modulated by DDR1 binding to collagen and occurred in part in the absence of IR/IGF1R phosphorylation. DDR1 silencing was ineffective in MCF7 knocked out for DDR1. Taken together, these results indicate that DDR1, acting in part independently of IR/IGF1R stimulation, might work as a novel regulator of BC metabolism and should be considered as putative target for therapy in BC.